2003
DOI: 10.1021/ie020954t
|View full text |Cite
|
Sign up to set email alerts
|

Gas−Liquid Flow Generated by a Pitched-Blade Turbine:  Particle Image Velocimetry Measurements and Computational Fluid Dynamics Simulations

Abstract: Axial flow impellers, like pitched blade impellers, are being increasingly used for gas-liquid systems in stirred vessels. In this work we have used particle image velocimetry (PIV) and computational fluid dynamics (CFD) models to investigate gas-liquid flow generated by a down-flow pitched blade turbine. PIV measurements were carried out in a fully baffled stirred vessel (of 0.19 m diameter) with a dished bottom. Angle resolved measurements of the flow field with and without gas dispersion were carried out. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 21 publications
4
29
0
Order By: Relevance
“…It may be noted that, while writing the time averaged mass balance, turbulent dispersion of dispersed phase was not considered. The numerical study of Khopkar et al (2003) indicated that the turbulent dispersion terms were significant only in the impeller discharge stream. Even near the impeller, the influence of dispersion terms on predicted results was not quantitatively significant (difference was less than 5%).…”
Section: Transport Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be noted that, while writing the time averaged mass balance, turbulent dispersion of dispersed phase was not considered. The numerical study of Khopkar et al (2003) indicated that the turbulent dispersion terms were significant only in the impeller discharge stream. Even near the impeller, the influence of dispersion terms on predicted results was not quantitatively significant (difference was less than 5%).…”
Section: Transport Equationsmentioning
confidence: 99%
“…Several attempts have been made in recent years to develop computational models of gas-liquid flows in stirred vessels (for example, Gosman et al, 1992;Morud and Hjertager, 1996;Bakker and van den Akker, 1994;Ranade and van den Akker, 1994;Ranade and Deshpande, 1999;Lane et al, 1999Lane et al, , 2000Khopkar et al, 2003). Most of these studies were restricted to very low gas flow rates with complete dispersion regime present in the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the magnitude of the Basset force and lift force are much smaller than that of the inter-phase drag force. A recent report by Khopkar et al [9] indicated that the effect of the virtual mass force was not significant in the bulk region of stirred tanks. Therefore, only the inter-phase drag force is considered in this work.…”
Section: Governing Equationsmentioning
confidence: 98%
“…These particles had a mean diameter of 20 mm and a density of 1.03 g/cm 3 . The seeding concentration was adjusted so as to achieve between 5 and 10 particles per interrogation area (Khopkar et al, 2003).…”
Section: Particle Image Velocimetrymentioning
confidence: 99%
“…In order to validate the CFD model at higher rotational velocities, PIV experiments were performed on a prototype CSAF unit. PIV is a powerful non-intrusive technique to obtain fluid velocities and has been used extensively as a stand-alone method for fluid flow studies (Hill et al, 2000;Hopkins et al, 2000;Pruvost et al, 2000;Shafiqul Islam et al, 2002;Xiong et al, 2003) as well as in conjunction with CFD models (Armenante et al, 1997;Khopkar et al, 2003;Ranade, 1997). These studies include using CFD and PIV to investigate hydrodynamics in bioreactors (Haut et al, 2003;Vial et al, 2002), highlighting the potential use of CFD in modeling and optimizing bioprocessing equipment.…”
Section: Validation Of Cfd Simulationsmentioning
confidence: 99%